2017
DOI: 10.1038/s41598-017-03536-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rare genetic variation of NLRP1 gene in familial multiple sclerosis

Abstract: The genetic etiology and the contribution of rare genetic variation in multiple sclerosis (MS) has not yet been elucidated. Although familial forms of MS have been described, no convincing rare and penetrant variants have been reported to date. We aimed to characterize the contribution of rare genetic variation in familial and sporadic MS and have identified a family with two sibs affected by concomitant MS and malignant melanoma (MM). We performed whole exome sequencing in this primary family and 38 multiplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…227 Distorted patterns of gene expression are a characteristic of many neurological diseases, such as MS, Alzheimer's disease and schizophrenia, and in various cases these altered gene expressions can be correlated straightforwardly to genomic/pathogenic variations. [228][229][230] These findings support the hypothesis of a robust association between anomalous gene expression and neurological diseases, suggesting that variants in non-coding regulatory elements are outstanding candidates for some of the observed missing heritability in neurological diseases. The identification of many null or expression variants of common HLA alleles will improve our understanding of their role in immune functions.…”
Section: Consideration Of Hla and Kir Regulatory Region Variation In supporting
confidence: 75%
“…227 Distorted patterns of gene expression are a characteristic of many neurological diseases, such as MS, Alzheimer's disease and schizophrenia, and in various cases these altered gene expressions can be correlated straightforwardly to genomic/pathogenic variations. [228][229][230] These findings support the hypothesis of a robust association between anomalous gene expression and neurological diseases, suggesting that variants in non-coding regulatory elements are outstanding candidates for some of the observed missing heritability in neurological diseases. The identification of many null or expression variants of common HLA alleles will improve our understanding of their role in immune functions.…”
Section: Consideration Of Hla and Kir Regulatory Region Variation In supporting
confidence: 75%
“…Several inflammasomes have been described to contribute to the pathology of MS, thus highlighting the overlap in function among different inflammasomes [25][26][27][28][29]. Here, we summarize the known contribution to date of the different inflammasomes to MS.…”
Section: Nod-like Receptors Absent In Melanoma-like Receptors and Msmentioning
confidence: 94%
“…NLRP1 variants have been reported in MS pathogenesis, but the precise mechanism of action remains undefined. A recent study identified a potentially causative amino acid substitution (glycine to serine) in NLRP1 that was associated with increased IL-18 and IL-1β production in familial MS patients [27]. However, a separate study was not able to identify pathological genetic variations in the NLRP1 gene [66].…”
Section: The Nlrp3 Inflammasomementioning
confidence: 99%
“…Several studies found an association between NLRP1 and vitiligo ( 91 ), autoimmune thyroid diseases ( 92 ), and type I diabetes ( 93 ). In a recent publication, Maver et al linked homozygous missense variant in NLRP1 gene (Gly587Ser) with familial forms of MS ( 94 ). Also, Bernales et al found several NLRP1 compound heterozygote mutations in MS patients ( 95 ).…”
Section: Nlrs As Positive Regulators Of Inflammationmentioning
confidence: 99%